FAKTOR‐FAKTOR YANG MEMPENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH PEMBIAYAAN GRIYA IB HASANAH DI PT.BANK BNI SYARIAH KANTOR CABANG BENGKULU - Karona Cahya Susena; Tito Irwanto; Erlin Priandi (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2019)
The purpose of this study is to find out the dominant factors that influence customer decisions in choosing financing from the hasanah hasanah at PT. Bank BNI Syariah KC. Bengkulu. The method used in analyzing research data is rating scale. The average respondent's answers to the four factors that influence the customer's decision in choosing financing from the hasanah at PT. Bank BNI Syariah KC.Bengkulu is 640 with very agree criteria, meaning that the average respondent strongly agrees that all the proposed factors, namely cultural factors, social factors, personal factors and psychological factors can influence the customer's decision in choosing financing from the hasanah at PT. Bank BNI Syariah KC. Bengkulu.